4. THE EFFICACY OF SECOND-LINE TREATMENT WITH DOCETAXEL FOR PATIENTS WITH NON-SMALL CELL LUNG CANCER STAGE IIIB-IV AT E HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the efficacy of second-line treatment with Docetaxel for patients with nonsmall cell lung cancer (NSCLC) stage IIIB – IV at E Hospital.Study subjects and methods: A retrospective, cross-sectional study including all patients withNSCLC state IIIB-IV and performance status of 0-1, who had had disease progression after first-linetreatment and received second-line treatment with Docetaxel in a single-regimen at 75 mg/m2 ofbody surface area every three weeks from 1/2016 to 12/2021 at E Hospital. Patients’ response wasevaluated using the “Response Evaluation Criteria in Solid Tumours,” “Disease Control Rate,” andProgression-free survival. In addition, the rate of patients who survived without disease progressionwas evaluated using the Kaplan-Meier curve and the association of different factors with that ratewas estimated using Cox’s proportional hazard regression.Results: 57 patients were included in this study (mean age 62.3±7.5 years, 46 were male). Our researchincluded 41 (71.9%) patients with a smoking history. Patients with stage IV disease accounted for96.4% of the study cohort. The most common histopathology was carcinoma, accounting for 80.7%.We found that after three cycles, 17.5% (n=10) had a response, no patient had a complete response,and the disease control rate was 66.7%. The median progression-free survival time was x months(interquartile range: x – y months).Conclusion: Patients with NSCLC stage IIIB – IV who had failed first-line therapy had a reasonablygood progression-free survival after receiving second-line treatment with Docetaxel at 75mg/m2 ofthe body surface.
Keywords: Non-small cell lung cancer, second-line chemotherapy, Docetaxel.